1984
DOI: 10.1017/s0021859600042180
|View full text |Cite
|
Sign up to set email alerts
|

The relative feeding value of kale (Brassica oleracea) containing normal and low concentrations of S-methyl-L-cysteine sulphoxide (SMCO)

Abstract: Kale of normal and low S-methyl-L-cysteine sulphoxide (SMCO) content was produced by growing the same cultivar in soils of normal (20-30 mg/kg) and low (5-10 mg/ kg) soil sulphate-S concentration. Compared with normal S plots, kale grown in low S plots showed little or no reduction in D.M. yield or total N content, but contained lower concentrations of inorganic sulphate, SMCO and glucosinolates.Replicated plots of normal and low SMCO kale were grazed by lambs for 12-week periods in two consecutive years, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Since cabbage contains SMCSO and its hydrolase (Mazelis, 1963;Pederson and Albury, 1969;Hall and Smith, 1983;Marks et al, 1992), and MMTSO is produced as a result of the enzyme reaction in a Brassica (Marks et al, 1992), the functionality of SMCSO was tested as a bacterial growth inhibitor in cabbage. SMCSO appears to be important in cabbage flavor (Date0 et al, 1957;Chin and Lindsay, 1993a) and to cause haemolytic anemia in livestock grazing kale (Barry et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Since cabbage contains SMCSO and its hydrolase (Mazelis, 1963;Pederson and Albury, 1969;Hall and Smith, 1983;Marks et al, 1992), and MMTSO is produced as a result of the enzyme reaction in a Brassica (Marks et al, 1992), the functionality of SMCSO was tested as a bacterial growth inhibitor in cabbage. SMCSO appears to be important in cabbage flavor (Date0 et al, 1957;Chin and Lindsay, 1993a) and to cause haemolytic anemia in livestock grazing kale (Barry et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Patridge et al (1985) also reported a reduced DMI when cabbage replaced barley in the diet of rabbits. This reduced DMI owing to the cabbage could be attributed to i) increased dietary fibre (aNDF, ADF and ADL) in cabbage containing diets, which might have reduced the palatability and feed intake of the diets; and ii) the presence of S-methyl-L-cysteine sulphoxide and glucosinolates, which are known to depress feed intake in ruminants fed diets containing brassica (Barry et al, 1984;Barry, 2013). According to Duncan & Milne (1992), adult sheep (45 -55 kg live weight) developed a resistance to brassica glucosinolates by degrading allyl cyanide in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 10.2 MJ metabolizable energy (ME)/kg DM, an 80.4% in vitro dry matter digestibility (IVDMD) (Mekasha et al, 2002) and 84% total digestible nutrients (TDN) (NRC, 2007) were reported for cabbage, making it a good source of nutrients for ruminants. However, cabbage is reported to contain S-methyl-L-cysteine sulphoxide and glucosinolates that depress intake by ruminants (Barry et al, 1984;Barry, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in B. oleracea, they increase from 6000 ppm in October to 9000 -12,000 ppm in winter, and the concentrations are highest in fl owers (Whittle et al 1976;Giovanni et al 1989). Low levels of soil sulfur result in as much as a 50% reduction of SMCO in the plant (Barry et al 1984). Concentrations of SMCO can be manipulated by nitrogen and sulfur fertilization practices, because it appears to function as a sulfur storage form (McDonald et al 1981).…”
Section: Smco Levels Variable; Increase With Plant Maturity; Highest mentioning
confidence: 99%